Structure and phase stability of novel 'twisted' crystal structures in carbon nanotubes - Wilson, M (2002)
The stability of novel, low dimensional, crystal structures formed by a simple alkali halide (KI) in single-walled carbon nanotubes are investigated using a simple computer simulation model. 'Twisted' crystals, not clearly related to the bulk structure, and found to form dynamically in specific tube diameters, are investigated. A phase diagram for the confined structures as a function of the nanotube pore size is calculated. Specific ranges of nanotube diameters are shown to favour these unique structures over structures related directly to those adopted by the bulk alkali halide. The high resolution transmission electron microscopy pattern for an example stable twisted crystal is simulated. © 2002 Elsevier Science B.V. All rights reserved.